Navigating change. Planning for societal and spatial transformations. Debates during the 12th AESOP Young Academics Conference. - Spijkerboer, Rozanne Charlotte; Forrest, Steven Ashley; Hilbers, Anne Marel (Taylor & Francis, 2018)
The 12th Young Academics Conference of the Association of European Schools of Planning (AESOP) was hosted at the University of Groningen from the 26th-29th March 2018. The aim of the conference was to understand how various disciplines within planning and related to planning are dealing with change. Researchers and practitioners presented their research on dealing with environmental, technological, population and political change, and approaches to study this. Understanding these processes and exploring appropriate planning approaches became apparent in framing as a bridging concept in the need for more explicit attention to the role of planners as actors in navigating change and the practice of respectful planning.
Keywords: Planungstheorie; Planungsforschung; Stadtplanung; Regionalplanung; Transformation; Sozialwandel; Strukturwandel; Planungsverständnis; Change Management; Tagungsbericht